The Flash Magazine - 2016 edition - University of Embu (University of Embu, 2016)
The pioneer issue of the University of Embu (UoEm) magazine, ambassador of the UoEm, The Flashlight UoEm Quarterly The Flashlight, is dedicated to celebrating the award of charter to Embu University College (then a constituent college of the University of Nairobi). The name of the magazine, The magazine will be the main forum for highlighting various activities at the University. Some of the highlights will be on academics, research and extension, planning and development initiatives, corporate social responsibility, students’ affairs, and linkages. Flashlight, is derived from the University of Embu Coat of Arms. The Sun’s Rays in the Coat of Arms stands for the role of the University as a disseminator of knowledge. The award of the charter makes UoEm a fully-fledged public university and sets it at par with other public universities in Kenya. The Flashlight illuminates the journey towards the charter award, the achievements and current status of the University and the future vision. The Editorial Board is proud to be associated with this pioneer issue of The Flashlight. The Editorial Board welcomes constructive contribution from all stakeholders to make the subsequent issues better. We wish to invite our partners from different sections and areas to support the magazine in terms of making it a platform for advertising, sharing information and research. The magazine shall be published on a quarterly basis and made accessible to all stakeholders through the print and online version.